2002
DOI: 10.1103/physreva.66.043414
|View full text |Cite
|
Sign up to set email alerts
|

Three-fluid description of the sympathetic cooling of a boson-fermion mixture

Abstract: We present a model for sympathetic cooling of a mixture of fermionic and bosonic atomic gases in harmonic traps, based on a three-fluid description.The model confirms the experimentally observed cooling limit of about 0.2 T F when only bosons are pumped. We propose sequential cooling -first pumping of bosons and afterwards fermions -as a way to obtain lower temperatures.For this scheme, our model predicts that temperatures less than 0.1 T F can be reached.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Various theoretical groups have considered improved cooling schemes [11], including optimizing the evaporation rate [12], using different trapping frequencies [13,14], or using laser rather than evaporative cooling [15,16,17]. We will restrict our investigation to a simple model of sympathetic cooling of a gas in a box, in which it will be shown that a minimum temperature arises naturally as a result of loss of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical groups have considered improved cooling schemes [11], including optimizing the evaporation rate [12], using different trapping frequencies [13,14], or using laser rather than evaporative cooling [15,16,17]. We will restrict our investigation to a simple model of sympathetic cooling of a gas in a box, in which it will be shown that a minimum temperature arises naturally as a result of loss of particles.…”
Section: Introductionmentioning
confidence: 99%
“…A similar semiclassical and discrete model for sympathetic cooling was put forward in Ref. [13], with the addition of features like collisional losses and spacedependent effects in the evaporation process, but without a determination of the limits of the cooling process. Using our idealized model, we shall then show that the argument based on the heat capacities is approximately correct for fermions cooled by an ideal Boltzmann gas [14], but incorrect when cooled by an ideal Bose gas below the Bose condensation temperature T c .…”
Section: Introductionmentioning
confidence: 99%
“…Shown is the temperature of a degenerate Fermi gas sympathetically cooled by a Bose gas with a condensate present, as a function of the number of bosons evaporated in a harmonic trap, that is, of the difference between the initial number of bosons N b,0 [assumed to fulfill Eqs (13). and(14)] and the final number N b .…”
mentioning
confidence: 99%
“…Sympathetic cooling has been recently considered by several theoretical groups [15][16][17][18][19][20][21][22]. It should be stressed, however, that the limitations due to particle losses have been addressed c EDP Sciences…”
Section: Pacs 0375ss -Degenerate Fermi Gasesmentioning
confidence: 99%
“…In this crossover, which has recently attracted a large attention, strong evidences for superfluidity have been observed [10][11][12][13][14]. Another obstacle appears when a Fermionic gas is sympathetically cooled using a Bose-Einstein condensate, since as a consequence of the superfluid properties of the condensate, the sympathetic cooling is limited to velocities larger than the sound velocity [15].Sympathetic cooling has been recently considered by several theoretical groups [15][16][17][18][19][20][21][22]. It should be stressed, however, that the limitations due to particle losses have been addressed c EDP Sciences…”
mentioning
confidence: 99%